Assessment of coagulation and fibrinolysis in families with unexplained thrombophilia - Wichers, Iris M.; Tanck, Michael W. T.; Meijers, Joost C. M.; Lisman, Ton; Reitsma, Pieter H.; Rosendaal, Frits R.; Büller, Harry R.; Middeldorp, Saskia (Thrombosis and Haemostasis, 2009)
Despite knowledge of various inherited risk factors associated with venous thromboembolism (VTE), no definite cause can be found in about 50% of patients. The lack of an intermediate phenotype in VTE impedes the discovery of new familial risk factors. We set out to define an intermediate phenotype for VTE by performing global coagulation analyses in unexplained thrombophilic families. Families were selected through a proband with VTE but without one of the known thrombophilic defects and at least one 1st or two 2nd degree family members with VTE. Clinical data were collected using a standardized questionnaire. Blood samples were collected for overall haemostasis assays (i.e. thrombin generation time [TGT], endogenous thrombin potential [ETP], prothrombin fragment 1+2 [F1+2] and activated protein C-sensitivity ratio [APC-sr] and clot lysis time [CLT]). Data were analysed using logistic regression. Coagulation assays were performed in 353 individuals of whom 41 (12%) had a history of VTE; these belonged to 17 thrombophilic families. Of the tested variables only the ETP was associated with VTE (odds ratio [OR] 1.03 for each % increase, 95% confidence interval [CI] 1.01–1.05). However, the relatively low number of cases does not firmly exclude the other assays as candidate intermediate phenotypes for venous thrombosis. We found that an increased ETP may serve as an intermediate phenotype for VTE and may be used to discover novel inherited risk factors by genetic linkage analysis.
Keywords: Coagulation factors; deep venous thrombosis; familial thrombosis; hypercoagulability; venous thrombosis